Alliance advantage : - Doz, Yves L. (Harvard Business School Press, 1998)
Partnerships between companies receive a great deal of attention from top managers and researchers at the time of their formation. This attention results largely from the common perception that the initial structuring of partnerships and establishment of common goals determines partnership outcomes and success.